Breast Cancer in Systemic Lupus Erythematosus - Cloutier, B. Tessier (2013)
OBJECTIVE: Evidence points to a decreased breast cancer risk in systemic lupus erythematosus (SLE). We analyzed data from a large multisite SLE cohort, linked to cancer registries. METHODS: Information on age, SLE duration, cancer date, and histology was available. We analyzed information on histological type and performed multivariate logistic regression analyses of histological types according to age, SLE duration, and calendar year. RESULTS: We studied 180 breast cancers in the SLE cohort. Of the 155 cases with histology information, 11 were referred to simply as ‘carcinoma not otherwise specified’. In the remaining 144 breast cancers, the most common histological type was ductal carcinoma (n = 95; 66%) followed by lobular adenocarcinoma (n = 11; 8%), 15 cancers were of mixed histology, and the remaining ones were special types. In our regression analyses, the independent risk factors for lobular versus ductal carcinoma was age [odds ratio (OR) 1.07, 95% confidence interval (CI) 1.01–1.14] and for the ‘special’ subtypes it was age (OR 1.06, 95% CI 1.01–1.10) and SLE duration (OR 1.05, 95% CI 1.00–1.11). CONCLUSIONS: Generally, up to 80% of breast cancers are ductal carcinomas. Though our results are not definitive, in the breast cancers that occur in SLE, there may be a slight decrease in the ductal histological type. In our analyses, age and SLE duration were independent predictors of histological status.